The Influence of a Realistic Mathematical Approach on Student Learning in Elementary Schools - Koerunnisa Koerunnisa; Rianto Rianto; Safitri Dwi Novita; Zahra Nurasih; Abdullah Abdullah; Aliah Aliah; Hamidah Fallo; Rasilah Rasilah (MASI Mandiri Edukasi, 2025)
This study investigates the impact of the Realistic Mathematics Education (RME) approach on students' critical thinking skills and learning outcomes in elementary schools. The research employs a literature review method by analyzing findings from previous studies, including experimental and quasi-experimental designs. The RME approach, characterized by its emphasis on real-world problems and contextual learning, enables students to connect mathematical concepts with practical applications, fostering critical thinking and problem-solving abilities. Various studies indicate that students using the RME approach exhibit significantly improved critical thinking skills compared to those taught using conventional methods. For example, one study showed an increase in the average critical thinking score from 63.29 to 80.29, with a significance value of 0.001 < 0.05, confirming the approach's effectiveness. Additionally, students demonstrated the ability to apply mathematical formulas in daily life and actively engage in learning activities, leading to higher academic achievement. The analysis highlights three key aspects of the RME approach: its ability to transform abstract concepts into relatable experiences, its adaptability to diverse student needs, and its effectiveness in promoting active participation. These attributes make RME a viable alternative for improving mathematics education in elementary schools. In conclusion, the RME approach provides a practical and effective solution for enhancing students' critical thinking skills and mathematical understanding, bridging the gap between theory and real-world application. This study recommends integrating the RME approach into mathematics curricula to achieve more meaningful and engaging learning experiences for elementary students.